2018
DOI: 10.1007/s10616-018-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

Selenious-β-lactoglobulin induces the apoptosis of human lung cancer A549 cells via an intrinsic mitochondrial pathway

Abstract: In this study, the cytotoxic activity of selenious-β-lactoglobulin (Se-β-Lg) and the anticancer mechanism were investigated in human lung cancer A549 cells in vitro. MTT assay showed that Se-β-Lg at 200 μg/mL exhibited a significant suppression effect on A549 cells and the maximum inhibition rate reached 90% after 72 h treatment. Flow cytometry analysis revealed that 200 μg/mL of Se-β-Lg induced cell cycle arrest at G/G phase. Cell apoptosis was induced via the generation of reactive oxygen species (ROS) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A similar mechanistic behavior was also observed for the anti-cancer activity of selenious-β-lactoglobulin (Se-β-Lg) in lung cancer cells (A549). 21…”
Section: Resultsmentioning
confidence: 99%
“…A similar mechanistic behavior was also observed for the anti-cancer activity of selenious-β-lactoglobulin (Se-β-Lg) in lung cancer cells (A549). 21…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is well known that apoptosis of tumor cells is often induced by anti-cancer drugs through the mitochondrial pathway. [33][34][35] Previous studies have confirmed that caspases and Bcl-2 family proteins, such as Bax and Bcl-2, serve important roles in the mitochondrial apoptotic pathway. [36][37][38] Mortenson et al 39 demonstrated that bortezomib triggered cell apoptosis in small cell lung cancer via decreasing Bcl-2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is like a barrier that initiates obstacles in the process of axonal regeneration. The intrinsic mitochondrial pathway involved in apoptotic cell death is initiated by caspase-dependent mechanisms [4]. After mitochondrial depolarization, these pathways participate in the interaction phenomenon of TNF and FAS on the cell surface, meanwhile, their specific receptors also contribute to it.…”
Section: Opinionmentioning
confidence: 99%